THE APPLICATION OF DIGITAL STORYTELLING TO IMPROVE STUDENTS’ LISTENING SKILL AT SMP NEGERI 6 TONDANO - Aditya Brayen Maramis; Sanerita Tresnawati Olii; Olga Rorintulus (Program Studi Pendidikan Bahasa Inggris, 2022)
This study aimed to improve the listening skill of eighth grade students of SMP Negeri 6 Tondano by using Digital Storytelling. This study used pre-experimental research with quantitative approach and one group pretest posttest design where the data was obtained from the students' listening test. The sample in this study were 27 students at SMP Negeri 6 Tondano. The findings of this study indicated a significant difference before and after using digital storytelling by obtained the mean score of 57.66 for the pre-test and 72.40 for the post-test with an increase of 25.56%. Wilcoxon analysis showed that there was a significant difference from the test before and after using digital storytelling with the Wilcoxon test results got Asymp. Sig. (2-tailed) = <.001 which is less than asymp. sig. (2-tailed) <0.05. Based on these findings, it can be concluded that using digital storytelling is effective for improving the listening skill of eighth grade students at SMP Negeri 6 Tondano